2021
DOI: 10.1186/s40168-021-01132-8
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of ancient dental calculus reveals unexplored diversity of oral archaeal Methanobrevibacter

Abstract: Background Dental calculus (mineralised dental plaque) preserves many types of microfossils and biomolecules, including microbial and host DNA, and ancient calculus are thus an important source of information regarding our ancestral human oral microbiome. In this study, we taxonomically characterised the dental calculus microbiome from 20 ancient human skeletal remains originating from Trentino-South Tyrol, Italy, dating from the Neolithic (6000–3500 BCE) to the Early Middle Ages (400–1000 CE).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 111 publications
(122 reference statements)
0
35
0
Order By: Relevance
“…Instead, the value of these ancient metagenomes may lie in providing insight into individual biofilm characteristics, particularly related to biofilm and microbial ecology. Another intriguing avenue of ancient dental calculus metagenome research is on the evolution of specific species and strains through the assembly and reconstruction of ancient metagenome assembled genomes ( 9 , 72 , 73 ). In contrast, the wealth of proteins and metabolites that are preserved in calculus may reflect biofilm community responses to altered oral environments such as dental disease or tobacco smoking ( 3 , 4 , 74 ), and could be used instead of the metagenome to study the role of health in shaping the oral microbiome in deep time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the value of these ancient metagenomes may lie in providing insight into individual biofilm characteristics, particularly related to biofilm and microbial ecology. Another intriguing avenue of ancient dental calculus metagenome research is on the evolution of specific species and strains through the assembly and reconstruction of ancient metagenome assembled genomes ( 9 , 72 , 73 ). In contrast, the wealth of proteins and metabolites that are preserved in calculus may reflect biofilm community responses to altered oral environments such as dental disease or tobacco smoking ( 3 , 4 , 74 ), and could be used instead of the metagenome to study the role of health in shaping the oral microbiome in deep time.…”
Section: Discussionmentioning
confidence: 99%
“…Dental calculus is a mineralized form of dental plaque that forms on the surface of teeth during life and persists in the archaeological record. Diverse microremains and biomolecules, including DNA, protein, and metabolites, are preserved within ancient dental calculus (1)(2)(3)(4)(5)(6)(7) and can be used to study oral microbial ecology and evolution through time (8)(9)(10), as well as provide evidence of past human activities (11). The majority of biomolecules present in calculus derive from dental plaque bacteria, and there is great interest in determining the feasibility of using these microbes to indirectly trace evidence of human behavioral or lifestyle changes and their impact on health through deep time.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the value of these ancient metagenomes may lie in providing insight into individual biofilm characteristics, particularly related to biofilm and microbial ecology. Another intriguing avenue of ancient dental calculus metagenome research is on the evolution of specific species and strains through the assembly and reconstruction of ancient metagenome assembled genomes (Brealey et al, 2020;Granehäll et al, 2021;Wibowo et al, 2021). In contrast, the wealth of proteins and metabolites that are preserved in calculus may reflect biofilm community responses to altered oral environments such as dental disease or tobacco smoking (Jersie-Christensen et al, 2018;Velsko et al, 2019Velsko et al, , 2017, and could be used instead of the metagenome to study the role of health in shaping the oral microbiome in deep time.…”
Section: Discussionmentioning
confidence: 99%
“…Dental calculus is a mineralized form of dental plaque that forms on the surface of teeth during life and persists in the archaeological record. Diverse microremains and biomolecules, including DNA, protein, and metabolites, are preserved within ancient dental calculus (Adler et al, 2013;Hardy et al, 2016;Hendy et al, 2018;Salazar-García et al, 2021;Velsko et al, 2019Velsko et al, , 2017Warinner et al, 2014) and can be used to study oral microbial ecology and evolution through time (Fellows Yates et al, 2021b;Granehäll et al, 2021;Ottoni et al, 2021), as well as provide evidence of past human activities (Radini et al, 2019). The majority of biomolecules present in calculus derive from dental plaque bacteria, and there is great interest in determining the feasibility of using these microbes to indirectly trace evidence of human behavioral or lifestyle changes and their impact on health through deep time.…”
Section: Introductionmentioning
confidence: 99%
“…Arizmendi Cárdenas et al reported that Centrifuge would be the most suitable tool for the identification of human DNA virus from ancient samples based on a simulation, with it demonstrating the highest sensitivity and precision when compared with other taxonomic binning tools such as Kraken2, DIAMOND, and MetaPhlAn2 [87][88][89]. Such tools have already been applied in several ancient microbiome studies and might be also useful for ancient viral genome classification and reconstruction [11,90]. In addition to sequence binning, preprocessed reads, PCR amplified fragments, and assembled contigs can be aligned to viral reference sequences using several alignment tools that detect ancient viral sequences, including the Basic Local Alignment Search Tool (BLAST), Burrows-Wheeler aligner (BWA), and MEGAN Alignment Tool (MALT) [91][92][93][94].…”
Section: Bioinformatic Analysismentioning
confidence: 99%